The Use Of Payment Cards In Kazakhstan: Analysis And Forecast - A. A. Kredina; O. V. Koshkina; László Vasa (Экономика: стратегия и практика, 2021)
The aim of the study is to analyze and forecast the use of payment cards for making non-cash payments through national payment systems in Kazakhstan. Based on this goal, a hypothesis was put forward that in Kazakhstan, there is a relationship between the number of payment cards and the volume of non-cash payments. This hypothesis was confirmed because of the study. The information base of the study was the data on payment cards, which were taken from the Statistical Bulletin of the National Bank of the Republic of Kazakhstan. Hypothesis testing was carried out using correlation analysis for three periods: 2009, 2016, 2020. The method of finding Pearson’s correlation in the SPSS program was used. The results showed a downward change in the relationship between the selected indicators and the amount of funds transferred over time. Also, in this study, a forecast was made for 2021-2023 for the indicators under consideration. To make a forecast for the indicators under consideration, a graphical method (polynomial trend line) was used. The resulting forecast shows the growth of cardholders and, consequently, the spread of the number of payment cards among the population in 2021-2023. The practical significance of this study is that the proposed methodology can help predict the dynamics of payment cards in any country in the world. Recommendations are also given for further improving the financial system, since increasing the transparency of monetary circulation in small-and-medium sized businesses will lead to a positive result in the implementation of the program for universal declaration of income in 2025.